Bilateral vestibular schwannomas in older patients: NF2 or chance?. Issue 6 (27th February 2015) - Evans, D G; Freeman, S; Gokhale, C; Wallace, A; Lloyd, S K; Axon, P; Ward, C L; Rutherford, S; King, A; Huson, S M; Ramsden, R T
Abstract : Background: Neurofibromatosis type 2 (NF2) is an autosomal dominant condition with high spontaneous mutation rate which predisposes to the development of multiple nerve sheath tumours (schwannomas), meningiomas and ependymoma. The cardinal feature and main diagnostic criterion for the diagnosis of NF2 remains the development of bilateral vestibular schwannoma (BVS). With increasing use of MRI screening the possibility of a 'chance' diagnosis of BVS has been mooted with a potential frequency of one in two million people in their lifetime. Until now, however, no evidence for such an event has been published. We aimed to demonstrate that chance occurrence can occur and to estimate its frequency among those with just BVS late in life. Methods: Two vestibular schwannomas from the same patient were DNA sequenced and underwent loss of heterozygosity analysis. Results: We show that a man who developed BVS, at ages 52 and 67 years developed these tumours sporadically by demonstrating that there were no molecular events in common between the two tumours. Furthermore from a database of over 1200 patients with NF2, we have estimated that ∼25% of cases of BVS over 50 years and 50% over 70 years of age where no other features of NF2 are present represent a chance occurrence rather than due to an underlying mosaic or constitutional NF2 mutation. Conclusions: Patients presenting with BVS later in life should be appraised of the potential likelihood they may not have NF2 and the resultant further reduction in risks of transmission to offspring.